Conservation of replication timing reveals global and local regulation of replication origin activity - Müller, Carolin A.; Nieduszynski, Conrad A. (Cold Spring Harbor Laboratory Press, 2012)
DNA replication initiates from defined locations called replication origins; some origins are highly active, whereas others are dormant and rarely used. Origins also differ in their activation time, resulting in particular genomic regions replicating at characteristic times and in a defined temporal order. Here we report the comparison of genome replication in four budding yeast species: Saccharomyces cerevisiae, S. paradoxus, S. arboricolus, and S. bayanus. First, we find that the locations of active origins are predominantly conserved between species, whereas dormant origins are poorly conserved. Second, we generated genome-wide replication profiles for each of these species and discovered that the temporal order of genome replication is highly conserved. Therefore, active origins are not only conserved in location, but also in activation time. Only a minority of these conserved origins show differences in activation time between these species. To gain insight as to the mechanisms by which origin activation time is regulated we generated replication profiles for a S. cerevisiae/S. bayanus hybrid strain and find that there are both local and global regulators of origin function.